2019
DOI: 10.1097/prs.0000000000006270
|View full text |Cite
|
Sign up to set email alerts
|

The Cutting Edge of Headache Surgery: A Systematic Review on the Value of Extracranial Surgery in the Treatment of Chronic Headache

Abstract: Background: Migraine is a debilitating neurologic condition, with a large socioeconomic impact. There is a subgroup of patients that does not adequately respond to pharmacologic management and may have underlying neuralgia. Surgical decompression of extracranial sensory nerves has been proposed as an alternative therapy. The aim of this article is to review the evidence for the surgical treatment of neuralgias. Methods: A systematic review was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…10,11 Deactivation of these peripheral trigger sites has been shown to improve symptoms. [12][13][14][15][16][17][18][19][20] Despite significant results after surgery, the differences in success rates and the subjective report of surgical outcomes in some studies have limited evaluation of its efficacy. Many of these patients undergo deactivation of nerves in multiple trigger sites; thus, determination of surgery success by specific trigger site has been difficult to report.…”
Section: Ementioning
confidence: 99%
“…10,11 Deactivation of these peripheral trigger sites has been shown to improve symptoms. [12][13][14][15][16][17][18][19][20] Despite significant results after surgery, the differences in success rates and the subjective report of surgical outcomes in some studies have limited evaluation of its efficacy. Many of these patients undergo deactivation of nerves in multiple trigger sites; thus, determination of surgery success by specific trigger site has been difficult to report.…”
Section: Ementioning
confidence: 99%
“…The recent literature shows that this procedure constitutes an effective treatment for types of headaches with an extracranial origin, and success rates between 68% and 95% are reported. 7 Before patients with these types of headaches are considered for surgical treatment, they are offered nonsurgical treatment options. 1 There are various nonsurgical treatments, including oral treatment and injection therapy.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] The recent literature provides the outcomes of surgical decompression in patients with headaches. 6,7 However, a review describing the efficacy of the nonsurgical treatment of patients is lacking. Therefore, this article aims to overview the current literature on the nonsurgical treatment options and evaluate the effectiveness of these treatments in patients with neuralgia and cervicogenic headaches.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent systematic reviews and meta-analyses have concluded that nerve decompression is effective in treating certain populations of individuals with headaches. 1518 1 review assessed surgical methods, finding that nerve decompression provided greater success rates than nerve stimulation which was in turn greater than radiofrequency ablation. 18 Other meta-analyses have summarized the outcome of headache elimination, reporting that the % of individuals with headache elimination ranges from 8.3% to 76% 16 and 8.3% to 83%.…”
Section: Introductionmentioning
confidence: 99%
“…18 Other meta-analyses have summarized the outcome of headache elimination, reporting that the % of individuals with headache elimination ranges from 8.3% to 76% 16 and 8.3% to 83%. 17 A third meta-analysis which also assessed the proportion of individuals with headache elimination reported a pooled proportion of 38% of individuals experience migraine elimination, although when assessing only randomized controlled trials the proportion was 21.46%. 15 Additionally, the proportion of individuals who experienced no relief of symptoms following surgery ranged from 3.9% to 33.3%.…”
Section: Introductionmentioning
confidence: 99%